2020
DOI: 10.1016/j.jcrysgro.2019.125299
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-beam epitaxy of GaSb on 6°-offcut (0 0 1) Si using a GaAs nucleation layer

Abstract: We studied and optimized the molecular beam epitaxy of GaSb layers on vicinal (001) Si substrates using a GaAs nucleation layer. An in-depth analysis of the different growth stages under optimized conditions revealed the formation of a high density of small GaAs islands forming a quasi-twodimensional layer. GaSb then nucleated atop this layer as three-dimensional islands before turning to two-dimensional growth within a few nanometers. Moreover, reflexion high-energy electron diffraction revealed a fast relaxa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The growth conditions of the GaSb layers presented in this paper are summarized in the Supporting Information, and more details can be found in reference. [ 57 ]…”
Section: Introductionmentioning
confidence: 99%
“…The growth conditions of the GaSb layers presented in this paper are summarized in the Supporting Information, and more details can be found in reference. [ 57 ]…”
Section: Introductionmentioning
confidence: 99%
“…The first is the serious lattice mismatch between the antimonide semiconductors and the Si substrate; the second is that the thermal expansion coefficients of the two materials are quite different, resulting in very large thermal stress during the crystal growth process; the last is the diverse polarity of the chemical bonds for the antimonides and Si. Due to the existence of the above three problems, antimonides grown on Si(100) substrates by MBE and MOCVD inevitably suffer from various defects, such as misfit sites, dislocations, antiphase domains, micro twin crystals, or micro cracks, which would degrade the device performance significantly in terms of high G-R currents and low QE [34,[181][182][183][184][185][186]. At present, only IQE Inc. of the United States reported that InAsSb-based MWIR PDs were successfully fabricated on a 6 inch Si substrate by using multilayer buffer layers, and an FPA detector was also prepared that achieved MWIR imaging at 77 K [187,188].…”
Section: Sb-based Ir Pds Integrated To a Si Platformmentioning
confidence: 99%
“…At present, only IQE Inc. of the United States reported that InAsSb-based MWIR PDs were successfully fabricated on a 6 inch Si substrate by using multilayer buffer layers, and an FPA detector was also prepared that achieved MWIR imaging at 77 K [187,188]. In addition, in the growth of InAs/InAsSb T2SL detectors on Si, although insitu thermal annealing [185], an offcut Si substrate [34,186], and AlSb buffer layers [37] can improve the crystal quality to a certain extent, the defect density with epitaxial antimonides on Si is still too high. More efforts could be made to solve this problem in order to achieve HOT or even uncooled detectors.…”
Section: Sb-based Ir Pds Integrated To a Si Platformmentioning
confidence: 99%
“…Gallium antimonide (GaSb) is a valuable material for applications in field-effect transistors, multi-junction solar cells, lasers, infrared detectors, and Shockley diodes. In addition, the molecular beam epitaxial is a common method to grow materials. Moreover, the reason why the development opportunity is taken by various electronic devices is that GaSb keeps some advantages of physical properties …”
Section: Introductionmentioning
confidence: 99%